Analisis ekonomi Islam meninjau praktek transparansi top up (penambahan pinjaman) perbankan - Rahma Yudi Astuti; Dhika Amalia Kurniawan (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This writing is motivated by the existence of customers who are stuck with the facilities provided by the bank, namely top up (additional loans), where the customer does not need to bother paying off the rest of the loan that should be repaid, the repayment fund is bailed out by the bank first, the customer will receive a new schedule and a new loan ceiling. Of course the bank will choose the criteria for customers who will be given top up facilities, namely the installment payment history is relatively smooth, precisely this is the base of the problem that many experienced by customers who do not understand about the top up offered by the bank that ends disastrous for customers. Lack of transparency about what the customer will go forward, which is applied by the bank to the customer so that many customers bear the losses caused by the top up. Lack of transparency about what the customer will go forward, which is applied by the bank to the customer so that many customers bear the losses caused by the top up. This research is a qualitative research with an evaluative-normative approach. The purpose of this research is to find out the extent of transparency applied by banks for top up, applying the principle of transparency in implementing Bank Indonesia regulations Number: 7/6 / PBI / 2005 about Transparency of Bank Product Information and how transparency practices are viewed from the Islamic economy. From these problems transparency to customers is very important in accordance with Islamic economics based on values and Islamic principles can be applied in all aspects of business life and transactions of the ummah. Compliance with regulations issued by the government, namely PBI no. 7/6 / PBI / 2005 which has not been fully implemented in banking in general. With the transparency applied in Islamic economics customers will know what their rights and obligations are. Transparency to customers is very important to prevent misunderstandings that can cause losses to customers.